Effect of pH on the Clarification of Bertoni Extract Using Alginate Beads - Cynthia R.A. Mahl; Silvia P.D. de Oliveira; Bruna B. da Silva; Gabriela da Igreja; Márcia R. Simões; Classius F. da Silva (Adsorption Science & Technology)
Stevia rebaudiana Bertoni is plant used for producing a natural sweetener. After extraction from leaves, stevia extract is dark in colour and must be clarified for better acceptance by consumers. Adsorption processes are widely employed in the clarification because they do not use organic solvents. In the present work, the use of alginate beads as an adsorbent was investigated. Experiments were carried out in a batch system in which the aqueous stevia extract was mixed with the alginate beads previously prepared by ionotropic gelation. The effect of pH on the adsorption process was evaluated and the performance of the beads was examined by colorimetric analysis (colour removal, turbidity removal and adsorption of stevia steviol glycosides), as well as by refractive analysis for determining the adsorption of soluble solids. The results showed that the alginate beads were capable of adsorbing both the stevia steviol glycosides and the pigments that colour the extract. The best results were observed at a pH value of 2.0.